2019
DOI: 10.3389/fimmu.2019.00299
|View full text |Cite
|
Sign up to set email alerts
|

Shorter TCR β-Chains Are Highly Enriched During Thymic Selection and Antigen-Driven Selection

Abstract: The adaptive immune system uses several strategies to generate a repertoire of T cell receptors (TCR) with sufficient diversity to recognize the universe of potential pathogens. However, it remains unclear how differences in the T cell receptor (TCR) contribute to heterogeneity in T cell state. In this study, we used polychromatic flow cytometry to isolate highly pure CD4 + /CD8 + naive and memory T cells, and applied deep sequencing to characterize corresponding T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 32 publications
5
23
0
Order By: Relevance
“…Our research reveals that enrichment of macrophages in HCC predicts poor prognosis. T cells (CD8+ T cells and CD4+ T cells) are the key immune cells that kill tumor cells by activating the immune system (47). For this reason, novel immunotherapies, such as PD-1 and PD-L1, have been designed to modulate the activity of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our research reveals that enrichment of macrophages in HCC predicts poor prognosis. T cells (CD8+ T cells and CD4+ T cells) are the key immune cells that kill tumor cells by activating the immune system (47). For this reason, novel immunotherapies, such as PD-1 and PD-L1, have been designed to modulate the activity of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The entire repertoire of NT was reported to be longer than the repertoire of memory 26 . However, we found that the top clones in NT were shorter than clones in other subsets in all datasets (Figure 4A; Supplemental Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…To amplify the rearranged CDR3 regions of the TCR‐β, a multiplex PCR system was designed using previously described methods. Briefly, the cDNA for each sample was amplified using a Qiagen Multiplex PCR Kit (QIAGEN) with 32 forward primers specific to the FR3 region and 13 reverse primers specific to the junction (J) region of the TCR, as published in our previous study 10,11 . The reaction conditions steps were as follows: 0·5 × Q solution, 0·2 μm Jβ R pool, 0·2 μm Vβ F pool and 1× Qiagen Multiplex PCR Master Mix.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the cDNA for each sample was amplified using a Qiagen Multiplex PCR Kit (QIA-GEN) with 32 forward primers specific to the FR3 region and 13 reverse primers specific to the junction (J) region of the TCR, as published in our previous study. 10,11 The reaction conditions steps were as follows: 0Á5 9 Q solution, 0Á2 lm Jb R pool, 0Á2 lm Vb F pool and 19 Qiagen Multiplex PCR Master Mix. The cycling conditions were as follows: 95°for 15 min, followed by 30 cycles of 94°for 30 s, 60°for 90 s, 72°for 30 s, plus a final extension of 5 min at 72°.…”
Section: Sequencing Of Tcr-b Repertoires and Bioinformatic Analysesmentioning
confidence: 99%
See 1 more Smart Citation